PENERIMA ASAM RETINOID a (a RETINOID ACID RECEPTOR) DI LEUKEMIA AKUT PROMYELOSITIK DENGAN BATANGAN (ROD) AUER - Adi K Aman; Tonny . (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2009)
Acute Promyelocytic Leukemia (APL) is a subtype of AML with a defined clinical course and biology that is distinct from otherforms of AML. The term M3-AML was assigned to the hyper granular promyelocytic leukaemia that is characterized by blast cells withazurophilic granules, bundles of auer rods and reniform or bilobed nucleus. Clinically, APL is related to disseminate intravascularcoagulation and abnormal fibrinolysis. Cytogenetically, APL may cause translocation on the promyelocytic leukaemia (PML) gene,and chromosome 15 and with the retinoic acid receptor α (RARA) gene, on chromosome 17. The diagnosis of APL is shown by bonemarrow morphologically The majority of cells in the bone marrow are abnormal, having some similarities with promyelocytes. Themalignant cells bear numerous large granules and several auer rods. Aspirates of bone marrow are also taken for cytogenesis evaluationand for detecting the translocation. A twelve years girl was admitted to the hospital with haemorrhage from the gums during 5 dayafter extraction of a tooth. On physical examination there is no organomegaly shown. The laboratory examination found normocyticnormochromic anaemia, leucopoenia and thrombocytopenia with 15% blast cell and 5% promyelocytes with multiple auer rods. Thebone marrow aspirates showed predominant of promyelocyte cells (70%) with multiple auer rods.